Peningkatan Komunikasi Interpersonal Karyawan melalui Psikoedukasi Berbasis Poster di Lingkungan Kerja - M. Jipung, Srikandi Gayatri.; Sambokaraeng, Tri Merdeka Putri; Haq, Fatwa L Dhiyaul; Resekiani Mas Bakar (Journal of Education Psychology and Social Development, 2025)
Employees in the workplace often face various interpersonal communication challenges, such as difficulties in expressing opinions, miscommunication, and minor conflicts among colleagues. This community service program aimed to enhance employees’ understanding of interpersonal communication principles through poster-based psychoeducation. A qualitative descriptive approach was employed, involving ten employees selected using purposive sampling. Initial data were collected through open-ended questions to identify participants’ communication problems, followed by an intervention using an educational poster containing key principles such as openness, empathy, positive attitude, and equality. Evaluation was conducted through open-ended questions to assess participants’ perceptions of the poster’s effectiveness. The results indicated that participants experienced several interpersonal communication barriers, and the poster was perceived as effective due to its concise content, clarity, and relevance to workplace situations. This visual psychoeducation increased participants’ awareness of the importance of interpersonal communication in fostering harmonious workplace relationships. The program demonstrates that simple visual interventions can be effective in improving communication quality in organizational settings.